The role of mixing sequence in shaping the 3D-printability of geopolymers - Mona Sando; Dietmar Stephan (Case Studies in Construction Materials)
This paper investigates the influence of sample preparation on a geopolymer composed of fly ash and ground granulated blast furnace slag, specifically designed for extrusion-based 3D printing. We examine the impact of geopolymerisation processes and evaluate their suitability for printing. Various methods, including penetration testing, slow penetration testing, uniaxial unconfined compression testing, ultrasonic wave transmission, heat flow analysis, and compressive strength testing, were employed to assess early structural buildup to gain insights into their effects on printability and buildability. Our results show that the way in which the liquid components are combined with the pecrusors is crucial for influencing the geopolymerisation rate and the geopolymer’s overall performance. By analysing the transition points of yield stress, calculating the Young’s modulus and examining green strength as an early indicator of compressive strength in the yet unset geopolymer, we accurately determine the printability duration using only small-scale laboratory tests, without physical printing tests. When liquid components are added individually, a high OH⁻ concentration locally increases pH and accelerates particle dissolution. By pre-mixing sodium hydroxide with water, the local pH decreases, the geopolymerisation rate is slowed down and the printability is prolonged. A homogeneous distribution of all liquids additionally leads to an even distribution of dissolved silicon ions. This accelerates geopolymerisation that the system becomes unprintable. Our measurements reveal that as structural condensation of the geopolymer begins, the rheological properties shift, rendering the material unsuitable for printing. The results demonstrate that optimised mixing strategies impact the suitability of the geopolymer for extrusion-based 3D printing.